Using archaeological data for the understanding of Late-Holocene Sea of Galilee’s level fluctuations - Matthieu Giaime; Michal Artzy (Scientific Reports, 2022)
Abstract In the Jordan Valley, reconstructed changes of the Sea of Galilee level have shown sharp fluctuations of the water elevation during the Holocene. In this paper, we provide new data originating from the excavations of Kursi Beach archaeological site located on the eastern shore of the Sea of Galilee and compare them with other data gathered from the archaeological site of Magdala, located on its western shore. Our data yield to constrain Sea of Galilee level changes between the Iron Age II (10th–9th centuries BCE) and the Crusader period (11th–12th centuries CE), a period of high interest for the archaeological community. We demonstrate that water level was around -212 to -210 m mean sea level (msl) for the Iron Age II period. Lake level rose to -208/-209 m msl during the Late Hellenistic/Early Roman period. Water level remained low (<-213/-214 m msl) from the Byzantine to the Crusader period (from 5th to 12th centuries CE). Our data provide new knowledge for the understanding of variations in the Sea of Galilee level in antiquity. We highlight that water level fluctuations must have been key factors taken into account in the habitation pattern.